A implementação da sociologia nas instituições privadas paranaenses : um estudo sociológico - Santos, Renata Oliveira dos (2011)
This master thesis aims to reflect the factors that have guided the actions of different social actors: directors, coordinators and teachers of sociology regarding the inclusion and the implementation of this discipline at "the botton line" of two private schools in the state of Paraná. The intention is to analyze what are the elements that allow curriculum matrix as diverse as the number of hours/lessons of Sociology at these private schools: Anjos Custódios in Marialva/PR and Pointer the Jandaia do Sul/PR. To understand this reality, it was necessary to rethink how education was often the subject of analysis and reflections of important social scientists throughout the development of the history of Brazilian education. In addition, it was thought about the path back and forth of Sociology to school, especially, in Paraná revealing what actions are being currently undertaken to develop Sociology teaching in and out of classrooms.